(untitled) (Physical Education, Health and Social Sciences, 2025)
Cytomegalovirus (CMV) is a globally prevalent herpesvirus that poses serious health risks, especially in immunocompromised individuals, transplant recipients, and neonates. Despite extensive efforts, a licensed CMV vaccine remains unavailable, largely due to the virus’s ability to establish latency and evade immune detection. This narrative review examines three promising vaccine platforms—viral vector-based, DNA-based, and mRNA-based technologies—that are currently at the forefront of CMV vaccine development. Viral vector vaccines, such as adenovirus and vesicular stomatitis virus (VSV) vectors, utilize genetically engineered viruses to deliver CMV antigens into host cells, stimulating potent cellular and humoral immune responses. However, their efficacy can be compromised by pre-existing immunity to the vector and concerns related to safety in high-risk groups. DNA-based vaccines offer a non-viral alternative by introducing plasmid DNA encoding CMV antigens directly into host tissues, where it initiates antigen expression and immune activation. These vaccines are stable, easy to manufacture, and inherently safe, but often require adjuvants or advanced delivery methods like electroporation to overcome their comparatively low immunogenicity. Meanwhile, mRNA vaccine platforms represent a transformative advancement in vaccinology. These vaccines encode key CMV proteins, such as glycoprotein B and immediate-early proteins, and are delivered via lipid nanoparticles. They elicit robust T cell-mediated and antibody responses, making them especially suitable for combating CMV’s immune evasion strategies. While mRNA vaccines offer rapid scalability and flexibility, their instability and storage requirements present logistical challenges. By comparing these vaccine modalities, the review underscores their respective mechanisms, advantages, and limitations, offering critical insights into the ongoing pursuit of an effective CMV vaccine. The integration of these emerging technologies with targeted immunological strategies holds promise for achieving long-term protection against CMV, particularly in vulnerable populations.